Cellular fibronectin promotes deep vein thrombosis in diet‐induced obese mice. (27th December 2020) - Dhanesha, Nirav; Jain, Manish; Doddapattar, Prakash; Undas, Anetta; Chauhan, Anil K
Abstract: Background: Overweight and obesity are significant risk factors for deep vein thrombosis (DVT). Cellular fibronectin containing extra domain A (Fn‐EDA), an endogenous ligand for toll‐like‐receptor 4 (TLR4), contributes to thrombo‐inflammation. The role of Fn‐EDA in the modulation of DVT is not elucidated yet. Objective: To determine whether Fn‐EDA promotes DVT in the context of diet‐induced obesity. Methods: Wild‐type (WT) and Fn‐EDA‐deficient mice were either fed control or high‐fat (HF) diet for 12 weeks. DVT was induced by inferior vena cava (IVC) stenosis and evaluated after 48 hours. Cellular Fn‐EDA levels in the plasma of venous thromboembolism (VTE) patients were measured by sandwich ELISA. Results: We found that cellular Fn‐EDA levels were significantly elevated in VTE patients' plasma and positively correlated with body mass index. HF diet‐fed WT mice exhibited increased DVT susceptibility compared with control diet‐fed WT mice. In contrast, HF diet‐fed Fn‐EDA‐deficient mice exhibited significantly reduced thrombus weight and decreased incidence (%) of DVT compared with HF diet‐fed WT mice concomitant with reduced neutrophil content and citrullinated histone H3‐positive cells (a marker of NETosis) in IVC thrombus. Exogenous cellular Fn‐EDA potentiated NETosis in neutrophils stimulated with thrombin‐activated platelets via TLR4. Genetic deletion of TLR4 in Fn‐EDA + mice (constitutively express Fn‐EDA in plasma and tissues), but not in Fn‐EDA‐deficient mice, reduced DVT compared with respective controls. Conclusion: These results demonstrate a previously unknown role of Fn‐EDA in the DVT exacerbation, which may be an essential mechanism promoting DVT in the setting of diet‐induced obesity.